MRSA Infection in Patients Hospitalized at Sanglah Hospital: A Case Series - A.A. Ayu Yuli Gayatri; Susila Utama; Agus Somia Agus Somia; Tuti P Merati (Acta Medica Indonesiana)
This is the first report of MRSA infection in Sanglah Hospital. We reviewed eight patients with MRSA infection from microbiologi laboratory records between January and May 2011, than followed by tracing medical records to obtained data of the patients. Five of cases with sepsis, 1 case with osteomyelitis, and the two others with mediastinitis and pneumonia. The patients were kept in private isolated room and barrier-nursing technique was strictly followed. Further action was culturing specimen taken from the patients nose, throat, axilla, and samples taken from the health care workers, with no MRSA colonization were found. Five patients demonstrated good respond to intravenous administration of either vancomycin or linezolide. Three were died due to septic shock before the laboratory culture and antimicrobial susceptibility availabled. All of the strains isolated more than 48 hours after admission and also demonstrated clinical risk factors for hospitalized acquired MRSA (HAMRSA). These strains had  resistance to ß-lactams but remain susceptible to many non ß-lactam antibiotics, as reported in some community acquired MRSA (CA-MRSA) isolates. Future study using molecular typing required to fully understand the magnitude and ongoing evolution of MRSA infections. Key words: MRSA, Antimicrobial susceptibility, treatment